2013
DOI: 10.1016/j.socscimed.2012.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities and subsequent risk of one or multiple abortions

Abstract: Although many studies have found an association between childhood adversities and mental health disorders, few have examined whether childhood adversities are linked to having abortions. This research investigates the association between a range of childhood adversities and risk of abortion in part to identify which adversities should be considered when examining the association between abortion and subsequent mental health. Using the U.S. National Comorbidity Survey-Replication (NCS-R), we tested the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Although care was taken to maximize accuracy of reporting and diagnoses, some mental health inaccuracy in diagnoses and abortion underreporting are likely 27,28 . For instance, in a similar sample from the National Comorbidity Survey-Replication, we found that only 44% of abortions were reported 21 ; this is similar to the level of underreporting of abortion from other national datasets 28,29 . It is not known how inaccuracy of mental health diagnoses or reporting of abortion influence the findings.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Although care was taken to maximize accuracy of reporting and diagnoses, some mental health inaccuracy in diagnoses and abortion underreporting are likely 27,28 . For instance, in a similar sample from the National Comorbidity Survey-Replication, we found that only 44% of abortions were reported 21 ; this is similar to the level of underreporting of abortion from other national datasets 28,29 . It is not known how inaccuracy of mental health diagnoses or reporting of abortion influence the findings.…”
Section: Discussionsupporting
confidence: 78%
“…We examined factors that have been shown to differ between women who have abortions compared with women who do not 14-21 : number of pre-first abortion or pre-first childbirth (henceforth pre-pregnancy) mental health problems, number of pre-pregnancy adverse exposures, pre-pregnancy miscarriage history, age at first pregnancy, race or ethnicity, and childhood economic status (low compared with not low). Number of pre-pregnancy mental health problems was determined by assessing whether each of the mental health disorders occurred before women’s first abortion (if having had an abortion) or first childbirth (if having had no abortions).…”
Section: Methodsmentioning
confidence: 99%
“…Our results suggest that the sexual health of first‐time adolescent mothers, as defined by these outcomes, varies by preconception CPS involvement. Self‐reported history of childhood abuse or neglect is an established correlate of increased rates of early sexual behavior and prior abortions . Our analysis extends these findings by using population‐based administrative data to document that adolescents who had a history of CPS involvement were significantly more likely than others to have a medically documented STD at the time of delivery and to report prior abortion.…”
Section: Discussionsupporting
confidence: 54%
“…This is reflected in the fact that close to 50% of teenage pregnancies end in abortion . Moreover, research on risky sexual behavior among adolescents with a history of reported maltreatment suggests that these young people may also have above‐average rates of pregnancy termination …”
Section: Introductionmentioning
confidence: 99%
“…Poverty, lower levels of education and other social inequalities have been associated with poorer mental health outcomes; they have also been linked to unwanted pregnancy and abortion, although findings have been mixed . Second, childhood abuse has been consistently associated with mental disorders and with abortion itself . Third, a history of mental disorders has repeatedly been found to be the most important predictor of mental disorders among women who have had an abortion …”
mentioning
confidence: 99%